Apoptotic effects on cultured cells of atmospheric-pressure plasma produced using various gases. (11th December 2015) - Tominami, Kanako; Kanetaka, Hiroyasu; Kudo, Tada-aki; Sasaki, Shota; Kaneko, Toshiro
Abstract: This study investigated the effects of low-temperature atmospheric-pressure plasma on various cells such as rat fibroblastic Rat-1 cell line, rat neuroblastoma-like PC12 cell line, and rat macrophage-like NR8383 cell line. The plasma was irradiated directly to a culture medium containing plated cells for 0–20 s. The applied voltage, excitation frequency, and argon or helium gas flow were, respectively, 3–6 kV, 10 kHz, and 3 L/min. Cell viability and apoptotic activity were evaluated using annexin-V/propidium iodide staining. Results showed that the low-temperature atmospheric-pressure plasma irradiation promoted cell death in a discharge-voltage-dependent and irradiation-time-dependent manner. Furthermore, different effects are produced depending on the cell type. Moreover, entirely different mechanisms might be responsible for the induction of apoptosis in cells by helium and argon plasma.